2013
DOI: 10.1186/1743-422x-10-145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of southern rice black-streaked dwarf virus on the development and fecundity of its vector, Sogatella furcifera

Abstract: BackgroundSouthern rice black-streaked dwarf virus (SRBSDV) threatens rice production in China and Vietnam. The virus is vectored by the migrating white-backed planthopper (WBPH, Sogatella furcifera) in a circulative, propagative, and persistent manner. A persistently-transmitted plant virus might affect its vector’s development and fecundity directly by infecting the vector itself and/or indirectly altering the host plant. This study evaluated the direct and indirect effects of SRBSDV on WBPH performance to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 28 publications
4
51
0
1
Order By: Relevance
“…Previous evidence has shown that persistent propagation of SRBSDV has only a limited adverse effect on its competent WBPH vector and is not pathogenic (49). Here, we found that SRBSDV became highly pathogenic to WBPHs when DCR2 was silenced during viral infection (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Previous evidence has shown that persistent propagation of SRBSDV has only a limited adverse effect on its competent WBPH vector and is not pathogenic (49). Here, we found that SRBSDV became highly pathogenic to WBPHs when DCR2 was silenced during viral infection (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies have indicated that the lifespans of female BPHs are shortened in SRBSDV-infected rice plants44. The lifespan of WBPHs carrying SRBSDV is less than 15 days at 25 °C45. Additionally, the salivary gland cells of BPHs infected by RRSV undergo programmed cell death46.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that the persistent propagation of plant viruses adversely affects insect vectors, including prolonging the nymphal stages, shortening adult longevity, reducing survival rate, or decreasing fecundity (22,59,63,77,102,103,123). These adverse changes could be attributed to direct effects of virus-insect interactions or indirect effects of the components from diseased plants.…”
Section: Adverse Effects Of Viral Infectionmentioning
confidence: 95%
“…It has become clear that viruses can manipulate their vectors either directly or by inducing changes in the host plants (12). The direct adverse effect of infection on insect fitness can hinder expansion of the viruliferous vector population (22,59,77,102). Such adverse effects of viral infection on insect development may also inhibit viral transmission by insect vectors.…”
Section: Ecological Impacts Of Virus-insect-plant Interactionsmentioning
confidence: 97%